2000
DOI: 10.1021/ie9905052
|View full text |Cite
|
Sign up to set email alerts
|

Extended Standing Wave Design Method for Simulated Moving Bed Chromatography:  Linear Systems

Abstract: For simulated moving bed (SMB) systems with significant mass-transfer effects, a model-based design method, which requires accurate mass-transfer parameters, was developed previously (Wu et al. Ind. Eng. Chem. Res. 1998, 37, 4023). An extended standing wave design method is developed in this study and tested using computer simulations and pilot-scale SMB experiments for the separation of phenylalanine (phe) and tryptophan (trp). In this method, propagation speeds of impurity waves are estimated from the efflue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 33 publications
0
51
0
1
Order By: Relevance
“…␤ is the logarithm of the ratio of the highest concentration to the lowest concentration of a standing wave in a particular zone. ␤ is an index of product purity and yield; the larger the ␤ value, the higher Ž the product purity and yield Ma and Wang, 1997;Xie et al, . 2000;Hritzko et al, 2002 . Compared with Eqs.…”
Section: Standing Wa©e Design For Nonideal Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…␤ is the logarithm of the ratio of the highest concentration to the lowest concentration of a standing wave in a particular zone. ␤ is an index of product purity and yield; the larger the ␤ value, the higher Ž the product purity and yield Ma and Wang, 1997;Xie et al, . 2000;Hritzko et al, 2002 . Compared with Eqs.…”
Section: Standing Wa©e Design For Nonideal Systemsmentioning
confidence: 99%
“…Both theoretical and experimental studies have shown that the SWD is efficient and guarantees high purity and high yield for binary Ž . separations Wu et al, 1998;Xie et al, 2000 and multicom-Ž . ponent separations Hritizko et al, 2002;Xie et al, 2002 with linear isotherms.…”
Section: Introductionmentioning
confidence: 99%
“…SMB 기술은 1960년대 초기 UOP 사 에서 개발하였고, 그 이후로 다양한 분야에 적용되기 시작했다 [1,2]. 대표적으로 정밀화학산업 [3,4], 제약 분야의 고순도 정제 [5], 아미노 산과 단백질 정제 [6,7], 제당 산업의 HFCS (high fructose corn syrup) …”
Section: 서 론unclassified
“…(1a)-(1d), led to several design methodologies, which are typically approximated and/or graphical, providing a better insight into the possible operating regions. Among other methodologies, one should mention the plate theory and the McCabe-Thiele diagrams [2], the analytical solutions for a linear adsorption isotherm system in the presence of mass transfer resistances [158] or for reactive systems [159], and the determination of wave velocities as in the standing wave design (SWD) [160,161].…”
Section: Designmentioning
confidence: 99%